Pregnancy Outcome in Amniotic Fluid Index 5 cm or less in Term Pregnancy at Tertiary Level Teaching Hospital, Birgunj, Nepal - Shrestha, Ruby; Chudal, Deepa; Shah, Ravi Kumar; Jain, Usha (Med Phoenix, 2022)
Introduction Oligohydramnios has increased incidence of fetal distress, meconium-stained liquor, prolonged labor, low Apgar score, low birth weight, admission to NICU, cord compression, birth asphyxia, and operative interference. The objective of the study was to determine the pregnancy outcome in amniotic fluid index 5 cm or less in term pregnancy. Materials and Methods This was a hospital-based cross-sectional study conducted at National Medical College & Teaching Hospital from June 2017 to May 2018. A total of 72 obstetric cases with AFI ≤ 5 cm and 72 cases with AFI > 5 cm with meeting the inclusion criteria were enrolled in the study after taking consent. Results Incidence of oligohydramnios was 2.2% out of 4318 deliveries and term oligohydramnios was 1.66%. AFI ≤ 5 cm was associated with increased induction of labor (p < 0.001), caesarean section (p = 0.01)), meconium stained liquor (p = 0.106), Apgar score <7 at 5 minutes (p = 0.001), NICU admission (p = 0.003), neonatal deaths (p = 0.053) were comparable with AFI >5 cm. Conclusion Amniotic fluid index ≤ 5 cm at term is an indicator of poor perinatal outcome. Women with AFI ≤ 5 cm can expect a good outcome if they have regular ANC visits and intrapartum monitoring than the AFI > 5 cm.